Potensi Ekonomi Lokal di Daerah Tertinggal dan Ketimpangan Antar Wilayah di Provinsi Lampung - Halvis Halvis; Zulfa Emalia (Jurnal Ekonomi Pembangunan, 2019)
This study aims to identify districts/cities that fall into the category of disadvantaged and analyze the level of regional inequality in Lampung Province. Another objective of this research is to identify sectors that are the basis of economies in regions that are included in the lagging category and identify appropriate policy strategies to develop industries that are economic bases in areas that are included in lagging types. The results showed that there were six districts included in the lagging category: West Lampung Regency, North Lampung, Pesawaran, Pesisir Barat, West Tuba, and Waykanan. The level of inequality in Lampung Province is in a low category, with the average theil index in 2011-2016 of 0.107. The economic base sector in most of the lagging regions in Lampung Province in the agriculture sector. After analyzing sector development, the most suitable strategy for developing the agricultural industry in Lampung Province is an aggressive strategy that focuses on opportunity and strength.